Aircraft maintenance & repair - Kroes, Michael J. (Aerospace science and technology series, 1993)
This text provides coverage of practical skills while building a foundation for more advanced learning. It offers a thorough presentation of all aspects of aircraft maintenance and repair, including information on new materials, structures, systems, and processes. This edition includes all the theoretical and practical information that students need for certification as FAA airframe technicians in accordance with Federal Aviation Regulations (FAR). In preparing the Sixth Edition, the authors reviewed FAR Parts 65 and 147 and appropriate Advisory Circulars, as well as realted Federal Aviation Regulations.